An Analysis of E-Marketplace Literature - Standing, S.; Standing, C.; Love, Peter (IE Med. European Institute of the Mediterranean, 2008)
Electronic marketplaces are important in both business to consumer and business to business electronic commerce. Business to business e-commerce e-marketplaces received a lot of bad publicity because of the perception of their use to drive down prices for suppliers. However, e-marketplaces remain significant in both practice and research. We regard it as timely to review the e-marketplace literature to determine the key features and patterns within the area. We analyze a large number of papers from the leading information systems journals. The research articles are classified according to five conceptual high level groupings: electronic markets theory; system perspective with a focus on the technology or functionality with the system; adoption and implementation issues; organisational implications; and broader e-commerce issues. Research on e-marketplaces has increased steadily since 1997. We observe that auction mechanisms have been a major focus of research but the more fundamental research questions still largely remain unanswered and hence there is a need for research that attempts to answer theoretical perspectives related to the efficiency of e-marketplaces and the also how to manage the use of e-marketplaces effectively in organizations.